Analisis Strategi Perusahaan Nvidia dalam Mempertahankan & Meningkatkan Keunggulan Kompetitif di Industri Semikonduktor Global - fahrezy dio fanany (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
The advancement of global digitalization and the acceleration of Artificial Intelligence (AI) have driven significant structural changes within the technology industry, particularly in the semiconductor sector. This transformation is characterized by the increasing demand for high-performance computing infrastructure, such as GPUs and AI accelerators, which serve as the foundational components for generative AI development and large-scale parallel computing. This study aims to analyze NVIDIA’s competitive strategies in enhancing firm value amid the dynamics of the global semiconductor industry. The research employs a literature review method by examining academic sources, industry reports, and relevant reputable publications. The analytical framework is based on the concepts of competitive advantage, Porter’s Generic Strategies, Porter’s Five Forces, the Resource-Based View (RBV), and the VRIN Framework. The findings indicate that NVIDIA’s success is not solely driven by the global surge in AI demand, but more importantly by its visionary and adaptive internal strategies. NVIDIA has effectively anticipated technological shifts by repositioning GPUs as general-purpose computing accelerators, undertaking bold strategic transformations, managing superior human capital, and diversifying its offerings through a high-value and difficult-to-imitate hardware–software ecosystem. These strategies have proven effective in creating sustainable competitive advantage, leading to improved corporate performance and market valuation. This study provides a conceptual contribution to understanding the competitive strategies of high-technology firms in the AI era; however, it is limited by its conceptual nature. Therefore, future research employing empirical approaches is recommended to strengthen the findings.